Association of CTLA-4 (+49A/G) gene Polymorphism with type 1 diabetes mellitus in Iraqi children: CTLA-4 (+49A/G) and type 1 diabetes mellitus - Al- Isawi, Hasanain Riyadh; Safi, Faiza; Muhammed , Hayder A. (Cellular and Molecular Biology, 2022)
CTLA4 is a regulator gene for T cells and relates to autoimmune diseases. By using a case-control method, CTLA4 functional single-nucleotide polymorphisms for potential associations with Type 1 diabetes mellitus in an Iraqi children’s population. ARMS-PCR method is used for genotyping +49AG (rs231775) variations in 60 obese children and 60 ethnically matched controls; all measured subjects were (fasting glucose, fasting insulin, and HbA1c). The glucose oxidase method is used to determine plasma glucose levels. The amounts of insulin in the blood were determined using a radioimmunoassay (RIA); Insulin resistance was measured using the HOMA-IR index. A HOMA-IR cut-off level of 2.5 was acceptable. There was no significant difference in allele and genotype frequencies between the groups, according to CTLA4 +49AG analyses. In conclusion, AA cases had a high frequency of A/A genotype than healthy participants but lower rates of A/G and G/G genotypes.